Infrared Remote Sensing of Surf-Zone Eddies - Marmorino, George O.; Smith, Geoffrey B.; Miller, W. David (IEEE journal of selected topics in applied earth observations and remote sensing, 2013)
Airborne infrared imagery is used for the first time to investigate characteristics of surf-zone eddies, occurring along an along-shore uniform beach. Eddies are found to have diameters of 100 to 150 m, an alongshore spacing of about 375 m (2.5 times the surf-zone width), and lifetimes of 40 min and longer. Eddies travel alongshore at speeds of \sim 0.3 to 0.5 m/s, at a distance from the shoreline of about 1.3 surf-zone widths. Eddies are also observed to move directly offshore, two surf-zone widths from the shoreline. Fine-scale thermal structure within an eddy includes \sim 6-m-wide cold patches, possibly the surface imprints of bottom-induced turbulence, and a small ( < 10-m wide) 'cold core', likely from accumulation of surfactant by radially inward surface flow. Visualization of an eddy is enhanced through flow deformation of surfactant slicks. In particular, narrow slicks appear to be wound-up by an eddy into spirals similar in form to those of a free vortex. In this sense, these nearshore eddies resemble ocean sub-mesoscale 'spiral eddies' as seen in synthetic-aperture radar and sunglint imagery.